La salida de campo chocó 2019 - I como estrategia para el desarrollo del aprendizaje significativo en la licenciatura en ciencias sociales: sistematización (2021)
Within the framework of the educational proposal of the degree in Social Sciences (LCS from now on) of the Antonio Nariño University, field trips (SC from now on) are usually organized, at least once a year, this being an important and innovative in the training of students. It should also be mentioned that these scenarios make it possible to improve teaching processes for the training of future graduates by being able to visit other scenarios that are part of their daily lives. In this sense, different departments have been visited, for example, Boyacá 2017 II, Putumayo 2018 I, Santander 2018 II, among others.